(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article discusses the impact of solar radiation on human health, its hygienic importance, beneficial and negative aspects, role in health care, exposure limits for different age and occupational groups, based on modern scientific approaches.